Makna Simbol Hau Monef Bagi Masyarakat Timor-Suku Dawan - Amsikan, Hendrikus Rinaldi (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2024)
Time changes, and so do humans. This statement remains relevant today, as people become increasingly aware of the close relationship between time and creativity. Within the framework of social life, this proverb emphasizes that throughout life, the ways individuals express themselves also evolve, which in turn influences their efforts to seek meaning related to themselves, others, nature, and God. This reality illustrates that humans are cultural beings capable of creating culture. In this context, the theme of this paper is